Evidence from Zakho Dairy Factory in Duhok Governorate - Hussain, Hussein; Ahmad, Miqdad (Humanities Journal of University of Zakho, 2020)
The sdudy aim to investigate the possibility to reduce the cost and adopting more effective modern methods based on cost-flow concept and the role played by the process of mapping cost flow in order to identify the defects in production processes and submitting most necessary proposals for making continuous changes which guarantee achieving a real reduction in productions cost and possibility of stability and competing other products in the market. The main aim of this research is to apply a cost-flow map through finding a way of accounting analysis for reducing costs without affecting the quality of the products. The researchers found a number of conclusions including: the basic idea of cost flow is to get rid of wastage in production process; achieving customer satisfaction; and achieving a clear effect in reducing products cost via applying cost-flow map in Zakho Dairy Factory as a research sample. In the light of research conclusions, the researchers presented a number of recommendations including: increasing the workers’ capacity in the factory through training courses; developing workers’ capabilities through discovering faults and defects in production systems; and reducing wastage through excluding activities that do not add value to the product and that would reduce the time and effort spent in production processes.